2015
DOI: 10.1002/2015jg003043
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from an alpine wetland on the Tibetan Plateau: Neglected but vital contribution of the nongrowing season

Abstract: The vast wetlands on the Tibetan Plateau are expected to be an important natural source of methane (CH 4 ) to the atmosphere. The magnitude, patterns and environmental controls of CH 4 emissions on different timescales, especially during the nongrowing season, remain poorly understood, because of technical limitations and the harsh environments. We conducted the first study on year-round CH 4 fluxes in an alpine wetland using the newly developed LI-COR LI-7700 open-path gas analyzer. We found that the total a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 106 publications
4
52
2
Order By: Relevance
“…For example, the study by Xu and Tian [] simulated 4.50 mg CH 4 m −2 h −1 in NE China, slightly lower than in situ measurements [ Song et al, ; Sun et al, ]. However, it was only 1.2 mg CH 4 m −2 h −1 in Zoige on the TP [ Xu and Tian , ], much lower than subsequent observational results in Zoige, Haibei, and Damxung on the TP (details in Table S1) [ Ding et al, ; Song et al, ; Sun et al, ; Wang et al, ; Li, , Chen et al , 2013; Yang et al, ; Hirota et al, ; Song et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the study by Xu and Tian [] simulated 4.50 mg CH 4 m −2 h −1 in NE China, slightly lower than in situ measurements [ Song et al, ; Sun et al, ]. However, it was only 1.2 mg CH 4 m −2 h −1 in Zoige on the TP [ Xu and Tian , ], much lower than subsequent observational results in Zoige, Haibei, and Damxung on the TP (details in Table S1) [ Ding et al, ; Song et al, ; Sun et al, ; Wang et al, ; Li, , Chen et al , 2013; Yang et al, ; Hirota et al, ; Song et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In situ measurements, primarily carried out using the static chamber‐gas chromatography method [e.g., Wang and Wang , ; Wang et al, ; Wei et al , ], have covered most types of China's natural ecosystems [ Chen et al, ; Wang et al, ]. There is also a growing number of EC studies in natural wetlands, e.g., in NE China [ Sun et al, ] and over the Tibetan Plateau (TP) [ Song et al, ], the major contributors of China's natural wetlands—the two regions contributed 84% of the national natural wetlands in the 2000s [ Niu et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this sensor was successfully deployed in an alpine wetland (mean annual 124 temperature = -1.1 °C) attaining data coverage up to 66% (Song et al, 2015). Generally, initiates heating based on air temperature thresholds, whereby the heater is maintained on for 145 temperatures below 4.5 °C.…”
mentioning
confidence: 99%
“…In addition, we found that the CH 4 emission flux in the P-hollow was much higher than the other four plots in the Zoigê Plateau wetland, suggesting that CH 4 in the P-hollow could be often transported to the surface by ebullition and CH 4 emission from the Zoigê Plateau wetland may be under estimated in the past. Whalen & Reeburgh, 1992;Huttunen et al, 2003;Inubushi et al, 2005;Chen et al, 2008;Glagolev et al, 2011;黄璞祎等, 2011;McEwing et al, 2015;Song et al, 2015), 二是因为气候变化 (IPCC, 2013;Munir & Strack, 2014) Lai, 2009;McEwing et al, 2015)。 这3个过程受 许多环境因子(温度、水位深度、底物活性和植物类 型)影响 (Mikkelä et al, 1995;丁维新和蔡祖聪, 2002;Inubushi et al, 2005;McEwing et al, 2015;Wei et al, 2015)。 由于湿地(如泥炭地)形成了多种生 态系统及其系统内异质性地貌 (Lai, 2009;Glagolev et al, 2011;Munir & Strack, 2014;Song et al, 2015;Wei et al, 2015), 不同水位深度条件下, 植被和土 壤温度具有差异, 进而导致CH 4 排放通量存在时空 变化 (Dise, 1993;王智平等, 2003;Hirota et al, 2004;Wei et al, 2015)。目前, 国外有关泥炭地微地 貌区CH 4 排放的研究较多 (Dise, 1993;Mikkelä et al, 1995;Waddington & Roulet, 1996;Glagolev & Shnyrev, 2008;Kalyuzhnyi et al, 2009;Munir & Strack, 2014) 斜率计算 (Mastepanov et al, 2008;McEwing et al, 2015), 回归方程决定系数R 2 ≥0.90; 当R 2 < 0.90时, 194.01 ± 50.07…”
mentioning
confidence: 99%